Quantitative analysis of submucosal excision depth in endoscopic resection for early Barrett’s cancer - Krause, Jenny; Rösch, Thomas; Steurer, Stefan; Clauditz, Till; Sehner, Susanne; Schumacher, Udo; Neuhaus, Horst; Messmann, Helmut; Schumacher, Brigitte; Probst, Andreas; Schachschal, Guido; Ehlken, Hanno; Vieth, Michael; Schmitz, Rüdiger (Endoscopy, 2021)
Background Following endoscopic resection of early-stage Barrett’s esophageal adenocarcinoma (BEA), further oncologic management then fundamentally relies upon the accurate assessment of histopathologic risk criteria, which requires there to be sufficient amounts of submucosal tissue in the resection specimens.Methods In 1685 digitized tissue sections from endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) performed for 76 early BEA cases from three experienced centers, the submucosal thickness was determined, using software developed in-house. Neoplastic lesions were manually annotated.Results No submucosa was seen in about a third of the entire resection area (mean 33.8 % [SD 17.2 %]), as well as underneath cancers (33.3 % [28.3 %]), with similar results for both resection methods and with respect to submucosal thickness. ESD results showed a greater variability between centers than EMR. In T1b cancers, a higher rate of submucosal defects tended to correlate with R1 resections.Conclusion The absence of submucosa underneath about one third of the tissue of endoscopically resected BEAs should be improved. Results were more center-dependent for ESD than for EMR. Submucosal defects can potentially serve as a parameter for standardized reports.